Observing autonomous product development: A grounded theoretical analysis of product innovation outside the boundaries of firms - Carrielle Somers; Jörg Henseler (Sustainable Futures)
The development of tools or products has always been fundamental to human progress, societal evolution and thereby a sustainable future. Thanks to the decreasing cost of 3D printing technology, we can develop complex products in the comfort of our home – and with the help of online communities. Despite this phenomenon, personal product development is less represented in product innovation literature, where profit-driven outcomes are prioritised. This gap in literature led to the main research question of this paper: how do individuals autonomously innovate products within open community settings? In order to find out, we interviewed makers (autonomous developers) of personal woodworking, metalworking, robotics, and 3D printed products.Through grounded theoretical discovery, we were able to answer the main question with three concepts – a range of product innovation, stages of autonomous product development and product innovation outcomes. The range of product innovation demonstrates three types of product development activities – copying, innovating and acquiring exclusivity. Four stages of autonomous product development were inferred motivations behind the range. Makers are motivated to evolve evolve a competence first. They then choose to innovate and finally increase individualistic development. These motivations result in product innovation outcomes during their development process. Product innovation outcomes are instances that lead to the introduction of something novel such as an idea, method or product. 16 outcomes are classified in this paper by the community and 13 by the individual developer.Our findings on autonomous product development contribute to future research in circular economy and sustainability. They present a foundation to examine development activities and motivations to upcycle household waste and minimises packaging. In addition, our research supports diffusion of innovations theory and social learning theory. Identifying autonomous development activities, motivations and outcomes show that even personal product innovations can be created, enhanced and influenced by open community systems. By demonstrating that complex scientific products can be learned in communities through social learning methods such as copying, personalising and acquiring exclusivity, this research enhances social learning theory.